2008
DOI: 10.5194/hessd-5-1821-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multi-objective optimization tool for the selection and placement of BMPs for pesticide control

Abstract: Abstract. Pesticides (particularly atrazine used in corn fields) are the foremost source of water contamination in many of the water bodies in Midwestern corn belt, exceeding the 3 ppb MCL established by the U.S. EPA for drinking water. Best management practices (BMPs), such as buffer strips and land management practices, have been proven to effectively reduce the pesticide pollution loads from agricultural areas. However, selection and placement of BMPs in watersheds to achieve an ecologically effective and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…China has been the world's largest consumer of pesticides for more than 10 years [4]. The latest research focus has changed from the fate and transport simulation into the source tracking and management measures [20][21][22]. However, Chinese pesticide research is mainly focused on determining the extent of pesticide residues in soil and water.…”
Section: Solute Dissolution From Surfacementioning
confidence: 99%
“…China has been the world's largest consumer of pesticides for more than 10 years [4]. The latest research focus has changed from the fate and transport simulation into the source tracking and management measures [20][21][22]. However, Chinese pesticide research is mainly focused on determining the extent of pesticide residues in soil and water.…”
Section: Solute Dissolution From Surfacementioning
confidence: 99%
“…8 The application of a calibrated watershed model to evaluate the effectiveness of various BMPs in improving water quality can also be computationally cumbersome. For example, Maringanti et al 14 have reported that optimizing BMPs in agricultural watersheds using the SWAT model may require a very large number of model runs (10 300 runs for an agricultural watershed having 500 farms and four BMPs possible for each farm). This computational burden is one of the primary reasons why the SWAT model has not been used to optimize BMPs in large agricultural watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…λ˜ν•œ μ‹œν—˜ν¬λ‚˜ κ²½μž‘μ§€μ—μ„œ ν‰κ°€λœ μ΅œμ κ΄€λ¦¬κΈ°λ²•μ— μ˜ν•œ λΉ„μ μ˜€μ—Όμ›μ˜ 저감 νš¨κ³ΌλŠ” λ‹€λ₯Έ μ§€μ μ΄λ‚˜ μœ μ—­μ— 적 μš©ν•˜κΈ° μœ„ν•΄μ„œλ‚˜ ν˜Ήμ€ μœ μ—­ λ‹¨μœ„μ—μ„œμ˜ 저감 효과λ₯Ό 뢄석 ν•˜κΈ° μœ„ν•΄μ„œλŠ” μ΅œμ κ΄€λ¦¬κΈ°λ²•μ— μ˜ν•œ λΉ„μ μ˜€μ—Όμ›μ˜ μ •λŸ‰ν™” κ°€ ν•„μš”ν•˜λ‹€ (Jang et al, 2010;Lee et al, 2014). λ³μ§šμ— μ˜ν•œ μ§€ν‘œν”Όλ³΅ λ“±κ³Ό 같은 μ΅œμ κ΄€λ¦¬κΈ°λ²•μ— λŒ€ν•œ 평가λ₯Ό μœ„ν•΄μ„œλŠ” λͺ¨λ‹ˆν„°λ§λΏλ§Œ μ•„λ‹ˆλΌ, 수문 λͺ¨ν˜•μ— μ˜ν•œ 평가도 ν•„μš”ν•˜λ‹€ (Bishop et al, 2005;Jang et al, 2010;Kim et al, 2006;Lee et al, 2014;Lee et al, 2012;Lee et al, 2000;Maringanti et al, 2009;Maringanti et al, 2008;Park et al, 2014;Srivastava et al, 2002). 2 )κ°€ 0.91둜 λ‚˜νƒ€λ‚¬ 으며, USLE P 인자λ₯Ό μΆ”μ •ν•˜κΈ° μœ„ν•œ νšŒκ·€μ‹(식 (1))κ³Ό 수 λ¬Έ λͺ¨ν˜•μ„ ν†΅ν•œ λ³μ§šλ§€νŠΈμ— μ˜ν•œ μœ μ‚¬λŸ‰ 저감 λͺ¨μ˜ 방법을 μ œμ•ˆν•œ λ°” μžˆλ‹€ (Jang et al, 2010 (Ahn et al, 2012;Park et al, 2013;Park et al, 2008).…”
unclassified